(untitled) (Interdisciplinary Studies Journal, 2025)
This article will address, through different theoretical perspectives, the contours that govern black masculinity. It will be verified, the way in which masculinity has controlled the behavior of black men in society, by delimiting spaces that must be occupied by them, generating images of violent beings, in addition to providing dysfunctional attitudes in their family environments. Masculinity is a social phenomenon that is linked to patriarchy, in which the man has a central figure in the various social spheres, mainly as the requirement to be the provider of the home. However, this masculinity reproduces discourses that are unhealthy in our social context, resulting in countless destructive aspects both for black men, for the education of black boys, and for women who become victims of this abusive relationship. To help us understand this entire epistemic and methodological path, which will analyze masculinity, we will rely on the contribution of the Colombian Mara Viveros Vigoya, who sought to detail the gaps left by the scarcity of studies on masculinity in the 1990s. Afro-American bell hooks will help us realize that the dysfunctional masculinity of black men can be deconstructed if we are willing to welcome them with affection and help them through the healing process. In addition, we will have the important contribution of the Afro-Brazilian researcher Lelia Gonzalez who, with her Afro-Latin American feminist studies, managed to establish a chain of valuable thoughts to the studies of whiteness in Brazil, and Patricia Hill Collins, an Afro-American intellectual, in which brought us black feminist epistemology, an important thought for studies of gender and race, and, mainly, regarding the dominant social forms of black subjectivity.